Aberrant Lower Extremity Arterial Anatomy in Microvascular Free Fibula Flap Candidates: Management Algorithm and Case Presentations. Issue 8 (November 2016) - Golas, Alyssa R.; Levine, Jamie P.; Ream, Justin; Rodriguez, Eduardo D.
Abstract : Abstract: An accurate and comprehensive understanding of lower extremity arterial anatomy is essential for the successful harvest and transfer of a free fibula osteoseptocutaneous flap (FFF). Minimum preoperative evaluation includes detailed history and physical including lower extremity pulse examination. Controversy exists regarding whether preoperative angiographic imaging should be performed for all patients. Elevation of an FFF necessitates division of the peroneal artery in the proximal lower leg and eradicates its downstream flow. For patients in whom the peroneal artery comprises the dominant arterial supply to the foot, FFF elevation is contraindicated. Detailed preoperative knowledge of patient-specific lower extremity arterial anatomy can help to avoid ischemia or limb loss resulting from FFF harvest. If preoperative angiographic imaging is omitted, careful attention must be paid to intraoperative anatomy. Should pedal perfusion rely on the peroneal artery, reconstructive options other than an FFF must be pursued. Given the complexity of surgical decision making, the authors propose an algorithm to guide the surgeon from the preoperative evaluation of the potential free fibula flap patient to the final execution of the surgical plan. The authors also provide 3 clinical patients in whom aberrant lower extremity anatomy was encountered and describe each patient's surgical course.